EFEKTIVITAS PEMBERIAN JELLY PORANG (Amorphophallus Muelleri) KOMBINASI JAMBU BIJI (Psidium Guajava) TERHADAP KADAR KOLESTEROL LDL PADA PASIEN HIPERKOLESTEROLEMIA - Darni, Joyeti; Wahyuningsih, Retno; Suhaema, Suhaema; Heryanto, Denisse (Jurnal Gizi dan Pangan Soedirman, 2023)
Hypercholesterolemia sufferers tend to be experienced at the age of 45-59 years and over 60 years. Hypercholesterolemia is caused by several factors, namely lifestyle, diet and physical activity. Guava and Porang tubers are one alternative to lower LDL cholesterol levels. Combination guava porang jelly is a snack made from porang flour and guava which is high in fiber and vitamin C. This study is an experimental quasy research. The subjects of the study amounted to 20 people consisting of 10 treatment groups and 10 control groups. The data collected were the intake of fat, fiber and vitamin C obtained by the method of recall of food consumption 1x24 hours before and during the intervention 4 times. Examination of LDL cholesterol levels using the CHOD-PAP method. Data were tested with the Mann-Whitney test to look at the effect of treatment on LDL cholesterol levels between the control group and the intervention group. The treatment group of LDL cholesterol levels before and during the study also decreased by 19,5 mg/dl while the control group by 7,7 mg/dl. There was no significant difference in LDL cholesterol levels after the intervention. However, there was a decrease in LDL cholesterol levels decreased by 19,5 mg/dl in the treatment group and 7,7 mg/dl in the control group.